Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1146/annurev-cellbio-100814-125241
|View full text |Cite
|
Sign up to set email alerts
|

The Hepatitis B Virus Receptor

Abstract: Hepatitis B virus (HBV) infection affects 240 million people worldwide. A liver-specific bile acid transporter named the sodium taurocholate cotransporting polypeptide (NTCP) has been identified as the cellular receptor for HBV and its satellite, the hepatitis D virus (HDV). NTCP likely acts as a major determinant for the liver tropism and species specificity of HBV and HDV at the entry level. NTCP-mediated HBV entry interferes with bile acid transport in cell cultures and has been linked with alterations in b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
57
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 151 publications
(179 reference statements)
1
57
0
2
Order By: Relevance
“…Ni et al reported that adding up to 2.5% DMSO to culture medium could increase HBeAg production from ccHBV infected HepG2/NTCP cells by up to 10-fold, which was about 100 times higher than produced by similarly infected HepaRG cells (18). This, combined with the no need for prolonged differentiation, makes HepG2/NTCP cells a more attractive system of in vitro infection (39). However, infection based on NTCP overexpression can be artificial, and the use of an exogenous promoter to drive NTCP expression prevents feedback transcriptional regulation of NTCP expression, which might be operative during the natural course of infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ni et al reported that adding up to 2.5% DMSO to culture medium could increase HBeAg production from ccHBV infected HepG2/NTCP cells by up to 10-fold, which was about 100 times higher than produced by similarly infected HepaRG cells (18). This, combined with the no need for prolonged differentiation, makes HepG2/NTCP cells a more attractive system of in vitro infection (39). However, infection based on NTCP overexpression can be artificial, and the use of an exogenous promoter to drive NTCP expression prevents feedback transcriptional regulation of NTCP expression, which might be operative during the natural course of infection.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that NTCP is a binding partner for the amino terminus of preS1 domain, it is possible that cytosolic (39), a related question is whether overexpressed NTCP suppresses virion secretion as well. Certainly, NTCP did not appear to markedly inhibit HBV virion secretion when HBV DNA replication was maintained at a high level through the strong CMV promoter (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Fortunately, the viral receptor was conserved in mammal species to a large extent, which may reduce the influence of this bias on the diversity of viral receptors. Secondly, due to the difficulties of identifying viral receptors (Li, 2015b;Pillay et al, 2016;Yan et al, 2012), the database of mammalian virus-host receptor interaction was still limited in its size, which hindered us from a more comprehensive survey of the correlation characteristics between viruses and viral receptors. More effective methods, either experimental or computational (Drayman et al, 2013), should be developed for identifying viral receptors, while the characteristics identified in this study may help such endeavors.…”
Section: Cc-by-ndmentioning
confidence: 99%
“…Aunque infecta a otros primates, su principal hospedero es el ser humano y se han identificado 10 genotipos (A-J) con diferente distribución geográfica, comportamiento clínico y respuesta a los tratamientos disponibles (11 El VHB ingresa al hepatocito por endocitosis mediante la interacción del HBsAg con el receptor polipéptido cotransportador de sodio-taurocolato (NTCP), con lo que pierde su envoltura (19,20). La nucleocápside es transportada hasta el núcleo donde su ADN parcial es madurado por proteínas celulares a un ADNccc, el cual es un minicromosoma muy estable que va a servir como modelo transcripcional para la ARN polimerasa II del hospedero (13,21).…”
Section: Ciclo De Replicación Viralunclassified